Strategi Pemasaran Kedai Kopi dengan Pendekatan SWOT Analysis (Studi Kasus pada Kedai Kopi Titan di Jakarta Selatan) - Aurel Rivanti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The positive trend reflected in the increase in coffee production and consumption could lead to increased competition among coffee shop operators. Titan Coffee Shop is one such business that has experienced sales challenges due to the impact of this competition. This study aims to identify the factors constituting the strengths, weaknesses, opportunities, dan threats in Titan coffee shop’s marketing efforts and to determine the most appropriate marketing strategies. The research design employs a qualitative approach using the case study method. Analysis utilizes the IFE matrix, EFE matrix, IE matrix, SWOT diagram, SWOT matrix, and QSPM. The results indicate the presence of 23 factors, comprising 8 strengths: a wide variety of menu options, high-quality raw materials, reasonably affordable prices, an attractive café concept, a spacious café area, a strategic location, excellent staff service, and adequate facilities; and 4 weaknesses: suboptimal promotional activities, lack of active online food delivery services, limited parking space, and proximity to competitors. Additionally, there are 7 opportunities: economic conditions, increasing public interest in coffee, changing lifestyles, the presence of communities, customer loyalty, government policy support, and technological advancements; and 4 threats: numerous similar competitors in the same area, the existence of substitute products, rising prices of coffee raw materials, and buyer bargaining power. The SWOT matrix analysis yielded 6 strategic alternatives: expanding sales distribution by opening new branches in other regions; hosting various in-store events; developing new products; enhancing marketing promotions; activating sales through online food delivery services; and reinforcing the café’s unique identity, with the strategy of enhancing marketing promotions being the top priority.